PENGARUH PRESSURE, OPPORTUNITY, RATIONALIZATION TERHADAP PERILAKU KECURANGAN AKADEMIK YANG DILAKUKAN OLEH MAHASISWA AKUNTANSI PADA PERKULIAHAN ONLINE (Studi Empiris Pada Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Negeri Malang) (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to examine whether simultaneously and partially the variables Pressure, Opportunity, and Rationalization can affect the act of academic cheating. This study uses quantitative methods by distributing questionnaires using google forms via online. This study took a sample of 2018 undergraduate students majoring in Accounting at the Islamic University of Malang and Accounting Students at the State University of Malang. The results obtained from this study are that the variables Pressure, Opportunity, Rationalization simultaneously have a significant positive effect on academic cheating behavior. Partially pressure has no significant effect on academic cheating behavior, partially opportunity has no significant effect on academic cheating behavior, and partially rationalization has a significant positive effect on academic cheating behavior.Keywords: Academic Cheating, Pressure, Opportunity, Rationalization